A Vicious Cycle: Probable Psychological Distress and Maladaptive Cognition as Barriers to Remediation Among Indonesian Medical Students Failing National Licensure - Gladys Putri; Mary-Jane Wood; Zahra Amir; Novalika Kurnia (Scientia Psychiatrica, 2025)
Introduction: Failure on high-stakes medical licensing examinations, such as the Indonesian Medical Doctor Competency Examination (UKMPPD), is a significant stressor. This study aims to delineate the current psychological profile of "repeat takers" (students who have failed at least once) to understand the psychological state associated with being in a cycle of academic failure. Methods: A multi-center, matched case-control study was conducted with 300 participants from five Indonesian medical faculties. The 'Case' group (n=150), recruited from remedial preparation courses, comprised students who had failed the UKMPPD at least once. The 'Control' group (n=150) consisted of peers from the same cohort who passed on their first attempt, matched for university, age, and gender. Psychological variables were measured cross-sectionally using the 10-item Connor-Davidson Resilience Scale (CD-RISC 10), the Brief COPE inventory, and the Self-Reporting Questionnaire-20 (SRQ-20) to screen for probable psychological distress. Results: Cases demonstrated a dramatically higher rate of probable psychological distress, with 62.0% of cases screening positive (SRQ-20 score ≥ 8) compared to 18.0% of controls (p < 0.001). Cases also reported significantly lower current resilience (Mean ± SD: 28.5 ± 5.4 vs. 34.1 ± 4.8, p < 0.001) and significantly greater use of avoidant/maladaptive coping (p < 0.001), driven specifically by Self-Blame (p < 0.001) and Behavioral Disengagement (p < 0.001). Binary logistic regression revealed that factors strongly associated with repeat-taker status included probable psychological distress (OR 5.2, 95% CI 3.1-8.7), lower resilience (OR 0.85, 95% CI 0.79-0.91), and Self-Blame (OR 2.1, 95% CI 1.4-3.2). Conclusion: The psychological state following licensure failure is characterized by a triad of high psychological distress, eroded resilience, and a reliance on self-blaming cognitive distortions. This profile, most parsimoniously interpreted as a consequence of initial failure, constitutes a formidable state of crisis and a critical barrier to successful academic remediation.